STUDENTS’ PERCEPTIONS TOWARDS THE USE OF AUDIO PODCAST IN TEACHING LISTENING - Dwi Mutmainah; Aseptiana Parmawati (PROJECT (Professional Journal of English Education), 2023)
This study was to find out student’s perceptions of the use of audio podcast in teaching listening. Podcast is a part of technology-based learning that can help learning activities to achieve teaching goals. This research is due to the problems found, some students are not interested in listening, and it is difficult to capture the content of the lesson. A descriptive qualitative method was used in this research. The study focus was on seventh-grade students at one of junior high school in Bandung, with a total sample was 22 students. The results show that the the students have positive perceptions about the use of the audio podcast in teaching listening.